The link between time orientation and religious orientation among American college students - Leach, Erica Cecelia Dawn (Mental health, religion & culture, 2017)
The purpose of this study was to explore how an individual’s religion relates to their time orientation. Specifically, we hypothesised (a) intrinsic orientation would positively correlate with future orientation, (b) extrinsic orientation would positively correlate with present-hedonistic orientation, (c) quest orientation would positively correlate with present-hedonistic and future orientations, (d) orthodox orientation would positively correlate with past positive orientation, and (e) secularism would positively correlate with past negative orientation, present-fatalistic and future orientations. Participants (n = 150) completed an online survey of time orientation and religious orientation. The results showed that perceptions of the past are strongly linked to religious orientation, with more positive perceptions being linked to the more traditional orientations, and less positive perceptions linked to the looser and secularist orientations.